Risk Analysis in Nurses Who Treat Patients with Infectious Diseases in Indonesia - Kristyanto, Bernadus; Anindyajati, Adhi (International Journal of Industrial Engineering and Engineering Management, 2025)
In this global pandemic of infectious diseases such as coronavirus-19 (COVID-19), Indonesia is one country that has a severe impact. In this situation, medical workers are arguably the most affected as they are the frontline in facing the pandemic. Their dedication and professionalism are put to a tough test; hence, they should stay healthy to provide treatment for the patients. However, in fact, many of them are infected by the coronavirus albeit the use of standard protective equipment and application of health protocols. In this study, a risk analysis on nurses working in inpatient wards for COVID-19 patients in quarantine was carried out. A Method of Human Error Analysis and Reduction Technique (HEART) was employed along with Fault Tree Analysis (FTA). The results indicated that fatigue, comorbid, and boredom were the factors associated with the highest risk of virus infection. These results suggest that management should pay attention to these factors in the work design of medical personnel, especially those who treat patients with infectious diseases such as COVID-19. In conclusion, work design must implement appropriate work shifts, as well as the implementation of strict health protocols.